The political economy of South Asian diaspora : patterns of socio-economic influence - Pillai, Gopinath (International political economy series (Palgrave Macmillan (Firm)), 2013)
"The South Asian diaspora is a diverse group who settled in different parts of the world, often concentrated in developed countries. There is an emerging trend of re-engagement of the diaspora in the South Asian region. Entrepreneurs in Japan and Singapore as well as the Malaysian Indian diaspora are involved in South India making the region a lucrative space for capital, talent and ideas. This volume expands into diasporic communities such as the Nepali community in Singapore and their contribution to their home economy through remittances. Beyond economics, the contributors explore how transnational politics overlap with religious ideologies amongst Pakistanis in United Kingdom and the Sathya Sai Baba movement which contributes to diasporic identity building in host countries. They also explore media and culture: in the last decade Bollywood films have portrayed life in the diaspora, and have featured the diaspora and Non Resident Indians (NRI) as fully formed stock characters and protagonists. The process of diaspora re-engagement has tremendous development implications for South Asian countries, both individually and for their regional integration"--